PENGGUNAAN LEMBAR KERJA SISWA BERBASIS MODEL PEMBELAJARAN GUIDED DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS - Jona, Pebri Hendrik; Permatasari, Rindah; Eveline, Erlin (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2023)
This research was conducted at Belimbing 1 State High School. This research aims to determine the effect of student worksheets based on the guided discovery learning model on critical thinking.This type of research is quantitative, using a quasi-experimental method with a nonequivalent control group design. The sample in this study consisted of 47 students, of which the control class consisted of 24 and the experimental class consisted of 23. Data collection techniques use written tests with research instruments in the form of essay questions. Data were analyzed using the t-test. Theresults of data analysis using the t-test in the control class and experimental class showed that Tcount was greater than Ttable, namely 5.201 2.01410 and Sig. (2-Tailed) = 0.000 0.05. It is concluded that there is a significant influence on the use of student worksheets based on the Guided Discovery Learning learning model on critical thinking skills. It was concluded that there was an increase in critical thinking skills after learning using student worksheets based on the Guided Discovery Learning learning model in the high category. In this way, student worksheets based on the Guided Discovery Learning learning model are able to foster students' critical thinking abilities. Keywords : Guided Discovery learning model, Critical Thinking Ability, Student Worksheets.